Der "ebenso effiziente Wettbewerber": Kosten-Preis-Vergleiche im Kartellrecht am Beispiel des Behinderungsmissbrauchs - Roth, David (Münchener Schr.z.Europäischen u.Internationalen Kartellrecht, 2017)
The „as efficient competitor“-standard has gained great practical significance when assessing exclusionary conduct – not least because of the „more economic approach“. The thesis investigates the standard’s historical and economic backgrounds, analyses its history of application and undertakes a critical assessment based on the aforementioned factors. The thesis follows a comparative law approach and is highly interdisciplinary. Thereby it majorly contributes to the controversial topic of how industrial organisation’s findings can be made viable for the application of law in light of versatile shortcomings. It adds to a clarification of the demanding prohibition rules on exclusionary conduct by providing important insights into the application of the „as efficient competitor“ test. By doing so, it aims at attracting the interest of academic scholars as well as professionals.